Mozart, Piano concertos no. 20 in D minor, K. 466, and no. 21 in C major, K. 467 - Grayson, David A. (Cambridge music handbooks., 1998)
"This guide to Mozart's two most popular piano concertos - No. 20 in D minor, K. 466, and No. 21 in C major, K. 467 (the so-called 'Elvira Madigan') - presents the historical background of the works and places them within the context of Mozart's compositional and performance activities at a time when his reputation as both composer and pianist was at its peak. The special nature of the concerto, as both a form and a genre, is explored through a survey of some of the approaches that critics have taken in discussing Mozart's concertos, ranging from analysis of pure structure to representations of the works as metaphors for human dramas. A theory of concerto form provides the basis for detailed accounts of the two concertos. The concluding chapter discusses a wide range of issues of particular interest to modern performers, including historical instruments, orchestra size and seating, cadenzas, basso continuo and improvised embellishments."--Jacket